2022
DOI: 10.1093/pubmed/fdac002
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to self-isolation among contacts of cases of COVID-19: a national telephone survey in Wales

Abstract: Background Self-isolation is challenging and adherence is dependent on a range of psychological, social and economic factors. We aimed to identify the challenges experienced by contacts of coronavirus disease 2019 (COVID-19) cases to better target support and minimize the harms of self-isolation. Methods The Contact Adherence Behavioural Insights Study (CABINS) was a 15-minute telephone survey conducted with confirmed contact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…The most reported outcomes were anxiety symptoms, 19,24,27,31,35,36,39,40,4245,47,48,50,51,54 depressive symptoms, 19,27,31,32,35,36,39,40,4245,4851 and general psychological symptoms. 19,20,25,27,30,31,34,37,39,43,46,48 Only three quantitative studies reported adaptive wellbeing outcomes. 31,46,48 Reasons for self-isolation were COVID-19 infection, 21,24,26,28,29,31,33,35,37,40,41,43,45,4749 suspected infection, 42 close contact with an infected person, 30,36,39,52,54 or a combination of these.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The most reported outcomes were anxiety symptoms, 19,24,27,31,35,36,39,40,4245,47,48,50,51,54 depressive symptoms, 19,27,31,32,35,36,39,40,4245,4851 and general psychological symptoms. 19,20,25,27,30,31,34,37,39,43,46,48 Only three quantitative studies reported adaptive wellbeing outcomes. 31,46,48 Reasons for self-isolation were COVID-19 infection, 21,24,26,28,29,31,33,35,37,40,41,43,45,4749 suspected infection, 42 close contact with an infected person, 30,36,39,52,54 or a combination of these.…”
Section: Resultsmentioning
confidence: 99%
“…19,20,25,27,30,31,34,37,39,43,46,48 Only three quantitative studies reported adaptive wellbeing outcomes. 31,46,48 Reasons for self-isolation were COVID-19 infection, 21,24,26,28,29,31,33,35,37,40,41,43,45,4749 suspected infection, 42 close contact with an infected person, 30,36,39,52,54 or a combination of these. 19,20,22,23,25,27,32,34,38,44,50,51,53 One study did not report a reason.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations